Health Workers in Samarinda City: An Examination of Their Distribution Based on Strategic Issues - Erwin Purwaningsih (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2022)
Providers and organizers of health care in the city are health professionals. The number of health workers needed in Samarinda has not yet been determined according to WHO guidelines, which is a ratio that compares the number of health workers to the population. The method used in this study is a descriptive-analytical non-experimental design (cross-sectional). Following the study's goals, research participants used secondary data from the Central Statistics Agency's report for Samarinda City in 2018/2019 in the form of social and population data.  Results: The number of doctors in Samarinda did not meet the WHO minimum requirements for the ratio of doctors to population of 1:2,500, with a ratio of 1:10,249 in the Samarinda Seberang district. The number of nurses is identical, but the standard ratio of 1:855 cannot be met; six sub-districts fail to meet the ratio, Sungai Pinang is the most effective sub-district in terms of achieving the nurse-to-population ratio. Apart from Samarinda Ulu and Samarinda Kota, the distribution of pharmacists has caught the attention of almost all districts in the city of Samarinda, a total of eight districts. Even one pharmacy in the Sungai Pinang district must serve 54,386 people.. Conclusion: The distribution of health workers in Samarinda is not equally distributed, owing primarily to external issues.